Pengembangan Buku Ajar Berbasis Problem Based Learning Pada Mata Kuliah Ilmu Sosial dan Budaya Dasar untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Helmi, Dewilna (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The implementation of the Merdeka Belajar-Kampus Merdeka policy in higher education presents new challenges, where students can explore learning beyond their study programs. Lecturers need to prepare teaching materials, such as textbooks, to assist students in enhancing their critical thinking skills. This study aims to develop a problem-based learning-based textbook for the ISBD course. The development method utilizes the ADDIE model, with data collection through questionnaires. Validation results indicate that this textbook received positive ratings from content experts (78.57%), media experts (77.14%), and instructional design experts (77.78%). Trials with lecturers and students showed good quality. The results affirm that the Problem-Based Learning-based ISBD textbook developed is suitable for use in the Geography Education Program at Pattimura University.